The Potential Therapeutic Effects of Tadalafil on the Endothelium in a Subarachnoid Hemorrhage Animal Model: Insights from Immunohistochemical Staining - Kwang Hyon Park; Hyon-Jo Kwon; Eun-Oh Jeong; Hyeon-Song Koh; Jeongwook Lim (Current Issues in Molecular Biology)
This study investigated the potential of phosphodiesterase type 5 (PDE-5) inhibitors, specifically tadalafil, in preventing the delayed cerebral ischemia (DCI) post-rupture of cerebral aneurysms. A total of 19 rabbits were used in this study, divided into different treatment groups, including nimodipine alone, tadalafil alone, and a combination of nimodipine and tadalafil. Both nimodipine and tadalafil showed some impact on reducing endothelial apoptosis in the basilar arteries, although the effects were not statistically significant. Notably, the nimodipine group exhibited significantly lower levels of Bax in the small arterioles compared to the SAH group. These findings suggest that while tadalafil may not directly prevent endothelial cell death like nimodipine, its neuroprotective properties hint at its potential utility in DCI treatment. Further research involving a broader range of apoptosis-related proteins is recommended to enhance our understanding in this area.